The Humanistic Form of Law in the Role of the Police and the Prosecutor's Office in the Implementation of Restorative Justice - Armasito Armasito; Nanda Nurul Farodiyah (ELQONUN: HUKUM KETATANEGARAAN ISLAM, 2025)
Restorative Justice one of the efforts to reform Indonesian criminal law in recent years has begun to resonate in courtrooms, emphasizing the restoration of the original state between perpetrators, victims, and the community, rather than simply punishment. Restorative justice's aims sound noble, as a “revolutionary” and collaborative policy, but its implementation in practice often falls short of its theoretical rosy. Restorative justice is a sweet promise, but the reality is not always ideal. The police and prosecutors, as subsystems of the criminal justice system, are competing to implement it. What is the role of the prosecutors and police in implementing restorative justice? It is urgent to explore this using a normative legal research approach, based on qualitative data analyzed from legal materials. Restorative justice is implemented through the process of terminating investigations and inquiries in the police and prosecutors' offices, in the form of a decree terminating prosecution. The application of restorative justice embodies a more humane approach to law enforcement; restorative justice is a solution, not an illusion, for justice itself.